Prediction of complex organic compounds activity with artificial neural networks. - E. V. Burljaeva; P. A. Ushakov (Тонкие химические технологии)
The analysis of neural networks applicability for complex organic compounds activity prediction is provided. The regulation algorithm is offered to improve the prediction properties of the networks.